Being as becoming: Play as a core concept in consumer-marketing studies - Wilson, Tony *; Choy, Tuck Yun *; Tan, Teck-Hong * (2014)
Purpose: Rejecting a stimulus-response approach to research on young persons as consumers subjected to marketing, this paper draws on phenomenology’s practices perspective. Embodied, equipped understanding is always already in use - in minimally monitored (tacit) play-like projecting, a participatory production of meaning. The paper investigates mall and media immersion as young people’s understanding-in-use: in discussion, they present visiting a massive shopping place as engaging with ludic location or a ‘second home’. Methodology: The paper reflects on Chinese Malaysian student narratives of consumer activity. Research commences from the ‘hypothesis’ of hermeneutics - or the philosophy of understanding-in-practice(s) as play-like - tested in a focus group. Visiting shopping mall or social media involves ‘ready-to-hand’ (little reflected on) ‘projecting’ and producing intelligibility, an integrating narrative, (dis)enabling ‘being-with-others’ (Heidegger). Talk in discussion enables theory to be empirically extended, grounding philosophical horizons of understanding. Findings: Our discussants’ consuming is structurally ludic, a play-like establishing of meaning from their ‘horizons of expectation’ (Jauss), equipped, and enabling. Visiting shopping malls manages goal-oriented or teleological meaning in embodied projecting and processing generic understanding of ‘entity’ (Heidegger) as equipment: people gain a purchase epistemologically in material acquisitions. ‘Ludicity’ is a core concept in consumer marketing interpretation, central to the practices perspective in business, media and sociological study. Implications: Managerial implications lie in enhancing marketing address to consumers, recognizing ludicity. The authors are now exploring understanding in visitor mall practices through the latter’s constructing cellphone images.